Information technology club management system - Ibrahim, Mohd Shukri; Kasim, Shahreen; Hassan, Rohayanti; Mahdin, Hairulnizam; Ramli, Azizul Azhar; Md Fudzee, Mohd Farhan; Salamat, Mohamad Aizi (Zibeline Internasional Publishers, 2018)
This Information Technology Club Management System is built to assist the IT staff of the Information Technology team to manage the club systematically and more effectively. The objective of this system is to develop and develop an online information technology club management system. In addition, this system is developed to generate more systematic and effective activities and programs. This system also helps not only members of the staff but also ordinary members, as well as ordinary members can interact and communicate with members of the post. The system is also able to provide systematic and efficient working advantages. Use of e-mail, as well as short messaging services, are also used in this system to facilitate the affairs of the power of affiliation. To achieve that objective, developers use a prototype method to develop and improve as a key to this system's revolt. In conclusion, this system reduces data filing on paper to be recorded using a computerized system. System developers use Adobe Dreamweaver and MYSQL applications and other applications like Adobe Photoshop to develop this system.